Réponses

2014-03-30T19:26:10+02:00
Bonsoir

A = x² +8x +16 - 8x -16 =
B = a² - 14a +49 + a² +14a +49 = 98
c =(2x+3 + 2x -3)(2x +3 -2x +3) = ( 4x )( 6) = 24 x
d = 9b² -30b +25 +30b = 9b² +25
E = 121 + 4x² - 121 = 4x²

32² = (30 +2)² = 30² +2x30 x 2 + 2² = 900 + 120 + 4 = 1024
21² = ( 20 +1 )² = 20² + 20 x 1 x 2 + 1² = 400 + 40 + 1 = 441
103² = ( 100 +3 )² = 100² + 2 x 3 x 100 + 3² = 10 000 + 600 + 9 = 10 609
19²  =( 20-1)² = 20² - 20 x 1 x 2 + 1² = 400  - 40 + 1 = 361
98² = (100 -2)² =100² - 100x2 x 2 + 2² = 10 000 - 400 +4 = 9 604
81 x 79 = (80 +1)(80 -1) = 80² - 1² = 6400 -1 = 6 399